2001
DOI: 10.1590/s1516-14392001000200005
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the Warren-Averbach method and alternate methods for X-ray diffraction microstructure analysis of polycrystalline specimens

Abstract: The fundamental parameters approach is used to simulate the instrument contribution to the X-Ray diffraction profile. This procedure eliminates the need to experimentally prepare a reference sample of the studied crystalline material when using the Warren-Averbach method to investigate microstrutural parameters. The Warren-Averbach method is also compared to the Balzar and Enzo methods, two other popular methods of size-strain analysis. The analysis was carried out using bohmite powder having two different nom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 26 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…However, one must remember that the crystal structures of the γ phase and the ε phase are quite similar, and thus both of them have XRD reflections either in the same 2θ angels or very close to each other. The average grain size of both types of samples after annealing was determined to be around 30 nm using the Warren-Averbach method for XRD data (Marinkovic et al, 2001). In Fig.…”
Section: Crystal Structure Characterization Of the Sensing Layersmentioning
confidence: 99%
“…However, one must remember that the crystal structures of the γ phase and the ε phase are quite similar, and thus both of them have XRD reflections either in the same 2θ angels or very close to each other. The average grain size of both types of samples after annealing was determined to be around 30 nm using the Warren-Averbach method for XRD data (Marinkovic et al, 2001). In Fig.…”
Section: Crystal Structure Characterization Of the Sensing Layersmentioning
confidence: 99%
“…In addition to the synthesis methodology, it has been observed that the architecture of bimetallic NPs can be modified by thermal treatment in the presence of H 2 , O 2 or Ar. 107 In the following sections, the reported application of bimetallic NPs in the selective hydrogenation of alkynes will be described according to the type of substrate used in catalysis and the metal combinations.…”
Section: Dilution Of the Active Phase: Introduction Of Modifiersmentioning
confidence: 99%
“…The initial slope of the curve giving A (l, sn) according to the length L columns is inversely proportional to the apparent size of the crystallites in a direction perpendicular to the plane (hkl) considered (Figure 1). This apparent size is given by the following equation [18,19]. From the Figure 1, the point of intersection of the initial slope of the curve with the x-axis (L) provides the size Df.…”
Section: Introductionmentioning
confidence: 99%